A STUDY ON HIGH SCHOOL STUDENTS’ PROBLEM IN MATHEMATICS SUBJECT (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This article tries to revealed about the high school students’ problem inmathematics subject. For this a data is collected through questionnaire method.A total ofseven high schools of the district Baksa of Assam is purposefully selected in the survey. Thequestionnaire method is conducted through the response sheet in order to get the data. As thedata is collected afresh, so this can be regarded as a primary data collection. why the majorityof students in this particular area are poor in mathematics subject is focused in this article.Some basic problems and factors are identified and trying to well defined.Based on responsesheet of the evaluated test, students’ performance is categorized into different sections. Thesecategories are considered as a fuzzy set based on the personal category. Since the collectedcan be regarded as imprecise data, so the process of defuzzification is used here to convert thedata into precise form. The centre of gravity (COG) or the centroid of area (COA) method isused to get the centroid of the data sets or to get the defuzzified value.